Combination of large volume sample stacking and dynamic pH junction for on-line preconcentration of weak electrolytes by capillary electrophoresis in comparison with isotachophoretic techniques - Horáková, Jana; Petr, Jan; Maier, Vítezslav; Znaleziona, Joanna; Stanová, Andrea; Marák, Jozef; Kaniansky, Dusan; Sevcík, Juraj (Journal of chromatography. A, 2007)
An on-line preconcentration capillary electrophoresis (CE) technique, which combines a large volume sample stacking with a dynamic pH junction technique, is introduced in this paper. This dynamic pH junction with co-electroosmotic migration is formed between sodium borate pH 9.5 and sodium phosphate pH 2.5 with 150 mM sodium dodecylsulfate (SDS). A full capillary based injection allows determination of weak acidic compounds at ppb concentration levels (achieved LOD for benzoic acid was 11 nmol L(-1)). The proposed preconcentration method was compared with ITP/ITP (LOD 120 nmol L(-1)), ITP/CZE (LOD 740 nmol L(-1)) and a simple CZE method (LOD 23,330 nmol L(-1)). The analytical potential of this method was assessed with juice test samples.
Keywords: elektroforéza kapilární; elektroforéza; kyselina benzoová; kyselina sorbová; Sorbic Acid; Benzoic Acid; Chromatography, Micellar Electrokinetic Capillary; koncentrace vodíkových iontů; chromatografie micelární elektrokinetická kapilární; Electrophoresis; Hydrogen-Ion Concentration; Electrophoresis, Capillary